2001
DOI: 10.1128/jb.183.6.2141-2144.2001
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Plasmid Rearrangement in Rhizobium leguminosarum bv. viciae VF39SM

Abstract: A rearrangement between the symbiotic plasmid (pRleVF39d) and a nonsymbiotic plasmid (pRleVF39b) in Rhizobium leguminosarum bv. viciae VF39 was observed. The rearranged derivative showed the same plasmid profile as its parent strain, but hybridization to nod, fix, and nif genes indicated that most of the symbiotic genes were now present on a plasmid corresponding in size to pRleVF39b instead of pRleVF39d. On the other hand, some DNA fragments originating from pRleVF39b now hybridized to the plasmid band at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Some authors emphasize the role of lateral genetic transfer in rhizobial evolution [39,40,[100][101][102][103], whereas others suggest the lateral transfer of nodulation genes occurred in minority of cases [104,105]. Moreover, frequent genetic transfer and recombination events were evidenced within species (between sublineages) in different models [11,36,42,43,49,101]. There is an agreement, that (a) in numerous cases the world distribution of microsymbiont strains followed the distribution of their hosts, and the symbiosis-associated part of the genome (localized on symbiotic plasmid or symbiotic island) was subjected to the most intense evolution and fitting [103,104,106,107], and (b) other (non-symbiotic) parts of the rhizobial genome changed together with the symbiosis-related regions [105,108].…”
Section: Changes In Rhizobial Populations Resulting From Plant-bactermentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors emphasize the role of lateral genetic transfer in rhizobial evolution [39,40,[100][101][102][103], whereas others suggest the lateral transfer of nodulation genes occurred in minority of cases [104,105]. Moreover, frequent genetic transfer and recombination events were evidenced within species (between sublineages) in different models [11,36,42,43,49,101]. There is an agreement, that (a) in numerous cases the world distribution of microsymbiont strains followed the distribution of their hosts, and the symbiosis-associated part of the genome (localized on symbiotic plasmid or symbiotic island) was subjected to the most intense evolution and fitting [103,104,106,107], and (b) other (non-symbiotic) parts of the rhizobial genome changed together with the symbiosis-related regions [105,108].…”
Section: Changes In Rhizobial Populations Resulting From Plant-bactermentioning
confidence: 99%
“…The frequency of plasmid transfer between rhizobial strains and the role of this genetic exchange in rhizobial evolution remains controversial [37][38][39][40]. However, the pool of plasmid replicons present in rhizobial cells is regarded as a (mostly) accessory genetic component which is evolving more rapidly than the chromosome [33], due to frequent changes (such as gene duplication, mutation or deletion) within particular replicons [41] or rearrangements between different replicons [42,43]. This distinction between the rhizobial chromosome and plasmids in the context of `evolutionary plasticity' and the role of these replicons in bacterial diversification resulted in the emergence of genomical concepts, which are similar to the pan-genome idea.…”
Section: Rhizobial Genomes -A Scheme For Extraordinary Strain Diversitymentioning
confidence: 99%
“…Fifty-seven of the groups contained only one plasmid based on their unique RAPD patterns. The patterns of the remaining 14 groups indicated possible additions, deletions or structural variants of genetically similar plasmids (Lilley et al, 1996 ;Zhang et al, 2001). While it has been suggested that fingerprinting by RFLP may overestimate plasmid diversity (Dahlberg et al, 1997), we believe that the use of RAPD-PCR coupled with subsequent DNA probe generation provides a robust and rapid approach for differentiating plasmid variation and diversity in natural microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, major DNA rearrangements between the chromosome and plasmids that are not involved in phase variation were also well documented for many bacteria, including the plant-associated bacterium Rhizobium. These genomic rearrangements arose at 10 Ϫ4 to 10 Ϫ3 ; they include deletion, amplification, inversion, and cointegration (13,26,40,41,60). Some of these rearrangements have biological consequences (26,39).…”
Section: Discussionmentioning
confidence: 99%